Bhanja - Au Yeong, Hui Wen (Nanyang Technological University, 2020)
As a child of a Gurkha, Shuvod Rai has spent 20 years of his life growing up in Singapore. In light of his father’s retirement from the service, we follow Shuvod’s journey as he helps his parents move back to Nepal. Even though Shuvod grew up in Singapore, and built a life for himself here, he might not be able to return. Amidst the uncertainties, Shuvod faces the question behind the notion of ‘home’. Where exactly is home to him? Is home the country he grew up in or the country reflected on his passport?